Fabrication and tribological behaviors of Ti3SiC2/Ti5Si3/TiC/Ni-based composite coatings by laser cladding for self-lubricating applications. (June 2020) - Yan, Hua; Liu, Kaiwei; Zhang, Peilei; Zhao, Jian; Qin, Yang; Lu, Qinghua; Yu, Zhishui
Highlights: MAX (Ti3 SiC2 ) and Ti5 Si3 silicide composite coatings were successfully prepared by in-situ synthesis laser cladding. Excellent self-lubricating properties of the coatings are attributed to Ti3 SiC2, Ti5 Si3 and TiC. Laser-clad Ti3 SiC2 /Ti5 Si3 /TiC/Ni-based composite coatings exhibit small amount of adhesive wear, plastic deformation. Abstract: In the work the in-situ synthesis of Ti3 SiC2 (MAX) phase and silicide reinforced Ni-based composite self-lubricating coatings from Ti-Si-C system and NiCrBSi powders were carried and initiated by laser cladding with use of 5 kW fiber laser beam with 3 mm spot. The microstructures of the laser-clad in situ synthetic self-lubricating coatings were analyzed by a scanning electron microscope (SEM) equipped with an X-ray energy dispersive spectrometer (EDS). An X-ray diffraction (XRD) spectrometer and an electron back-scattered diffraction (EBSD) were used for determination of the reaction products in the composite coatings. The friction and abrasion behavior of the coatings were evaluated at room temperature by a dry sliding friction tester. The results indicate that in-situ chemical reactions took place between elements Ti, Si and C in the laser molten pool, and the reaction products included Ti3 SiC2, Ti5 Si3, and TiC ceramics as well as TiNix compound. Finally, three laser-clad Ti3 SiC2 /Ti5 Si3 /TiC/Ni-based composite coatings with the total thickness about 1 mm were fabricated on Ti6Al4V alloy. The average microhardness of the three coatings was 703.2 HV0.2, 751.9 HV0.2 and 850.6 HV0.2 respectively, which has been significantly improved, compared with the hardness of Ti6Al4V substrate (about 360 HV0.2 ). The average friction coefficient of the Ti3 SiC2 /Ti5 Si3 /TiC/Ni-based composite coating (50 wt% Ni25/50 wt% Ti-Si-C) reduced to 0.33 at room temperature, and it exhibited the wear rate of 13.5 × 10 −5 mm 3 N −1 m −1 . The laser cladding Ti3 SiC2 /Ti5 Si3 /TiC/Ni-based composite coatings characterized by small amount of adhesive wear, plastic deformation and relatively smooth wear surface could be observed.